Risk of perinatal mortality among the offspring of workers employed at production with radiation hazards - S.F. Sosnina; P.V. Okatenko; M.E. Sokolnikov (Analiz Riska Zdorovʹû, 2023)
Studies that address risks of perinatal mortality among the offspring of people exposed to ionizing radiation in the workplace are significant for developing hygienic standards at production facilities with radiation hazards.